KREATIVITAS IKLAN SEDERHANA DALAM MENCIPTAKAN EXPOSURE DI INSTAGRAM - Handini, Handini (SOURCE : Jurnal Ilmu Komunikasi, 2024)
Simple, creative ads can create significant exposure on Instagram. Exposure in the context of marketing is the extent to which the audience or potential consumers are exposed to marketing messages or advertisements. In simple terms, exposure describes the number or frequency of a brand, product, or promotional message being seen by the target market. @sumargodenny account is owned by the actress whose full name is Denny Sumargo. The subject of this study is the Instagram account of individuals who are actively marketing through simple and creative advertising. The object of the study includes a variety of simple ads that have been uploaded by these accounts, as well as the level of exposure generated from those ads. The research was carried out on uploads starting from July 1 to August 29, 2024. In two months there were 22 uploads with 18 uploads in the form of advertisements, 3 personal uploads and 1 repost upload from his Youtube Channel. Creative advertisements made by Denny Sumargo are in the form of images or photos and short videos. Creativity is the main key to success in creating exposure by creating a simple, short advertising concept but the message conveyed is easy to understand. Create visualizations, and narratives that are funny, humorous and always have a plot twist in the story of the advertising video